Citizen Guarantees in Determining National Leaders Through Elections and Democratic Integrity - Dewi Iriani; Muhammad Fauzan; Sri Hastuti Puspitasari; Arief Budiono (Jurnal Dinamika Hukum, 2023)
Indonesia held presidential, regional head, and legislative elections (elections) in 2019. Many Indonesians are apathetic towards elections. The problems in this research are: How can citizens guarantee their right to determine regional leaders through elections and what obstacles do citizens face in choosing democratic leaders who have integrity? This is normative legal research conducted by tracing the regulations related to the problem under study. Citizen guarantees in determining regional leaders through elections are regulated in Law no. 39 of 1999 concerning Human Rights, Article 23 paragraph (1); Article 43 paragraph (1); Article 1, paragraph 3); Articles 28D, E, and J of the 1945 Constitution; and Law no. 7 of 2017 concerning Elections.Keywords: Democracy, Guaranteed Elections, Regional Leaders, Citizens.